КОМУНАЛЬНА ВЛАСНІСТЬ ЯК ПЕРЕДУМОВА РЕАЛІЗАЦІЇ ГОСПОДАРСЬКОЇ ПРАВОСУБ’ЄКТНОСТІ МІСТА - Dzhabrailov, R.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article advances the arguments that the communal property is an economic basis for economic management, namely of a city. It has been determined that the precondition for realizing economic legal personality of a city is the recognition of the right to communal property by its subject. The necessity is expressed to introduce into the Economic Code of Ukraine the classification of objects of the right to city’s communal property taking into account the degree of engagement in the economic turnover.